2018
DOI: 10.12809/hkjr1816960
|View full text |Cite
|
Sign up to set email alerts
|

Update on Ultrasound Diagnosis for Thyroid Cancer

Abstract: Thyroid nodules are prevalent in the general population. Distinguishing benign and malignant thyroid nodules is a clinical challenge. Although ultrasonography is commonly used for the assessment of thyroid nodules, previous studies have found that its usefulness is controversial. Therefore, there is a need to assess the clinical value of ultrasonography reported in the literature. This article reviews the literature on the clinical value of greyscale ultrasonography, colour and power Doppler ultrasonography, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…Bojunga found in his review that elastography was predominantly useful as a negative predictor for malignancy (a high NPV 93%–99%) 32 . Baig et al also describes elastography as an adjunct to standard‐ and Doppler imaging and emphasizes the need for larger studies to study its effects 100 . Du et al found that elastography combined with a RSS was superior to using only the RSS for differentiating small thyroid nodules 101 .…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Bojunga found in his review that elastography was predominantly useful as a negative predictor for malignancy (a high NPV 93%–99%) 32 . Baig et al also describes elastography as an adjunct to standard‐ and Doppler imaging and emphasizes the need for larger studies to study its effects 100 . Du et al found that elastography combined with a RSS was superior to using only the RSS for differentiating small thyroid nodules 101 .…”
Section: Diagnosismentioning
confidence: 99%
“…32 Baig et al also describes elastography as an adjunct to standard-and Doppler imaging and emphasizes the need for larger studies to study its effects. 100 Du et al found that elastography combined with a RSS was superior to using only the RSS for differentiating small thyroid nodules. 101 Aghaghazvini et al…”
Section: Future Trends-tissue Characteristicsmentioning
confidence: 99%
“…A thyroid nodule (TN) is a mass of solid, fluid-filled, or a combination of the two that develops from aberrant growths of thyroid cells within the thyroid gland. TNs are prevalent, affecting 20% to 76% of the population [1]. The incidence of TNs have been measured at 2-6% by physical examination, 19-35% by imaging, and 8%-65% by autopsy [2].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid nodules (TNs) are abnormal growths of thyroid cells that form solid, fluid-filled, or mixed masses within the thyroid gland. TNs are common and are found in 20% to 76% of the population 1. The prevalence of TNs has been reported to be 2-6% with palpation, 19-35% with US, and 8%-65% on autopsy 2.…”
Section: Introductionmentioning
confidence: 99%
“…US is the first-line imaging modality used to identify and characterize TNs. Gray-scale ultrasonography (GSU) imaging features of TNs are reliable in differentiating benign from malignant nodules 1,7. The elastic properties of TNs showed malignant nodules to be stiffer than benign nodules and this held out the promise of discrimination between benign and malignant nodules with higher diagnostic accuracy than GSU 1,8…”
Section: Introductionmentioning
confidence: 99%